172. Antimicrobial Stewardship in High-risk Pediatric Patients. (26th November 2018) - Goldman, Jennifer; Yu, Diana; Newland, Jason; Jackson, Mary Anne; Weddle, Gina; Mcculloh, Russell; Myers, Angela; Day, James; Lee, Brian R
Abstract: Background: The clinical impact of antimicrobial stewardship programs (ASP) on children admitted to the intensive care units (ICU) or oncology wards is unknown. The objective of this study was to determine whether following ASP recommendations improved clinical outcomes in pediatric ICU and oncology patients. Methods: We performed a retrospective cohort study to evaluate the relationship between ASP recommendation(s) agreement and patient outcomes (hospital length of stay [LOS], 30-day mortality, hospital readmission within 30 days, and hospital-onset Clostridium difficile infection [HO-CDI]) in a high-risk (HR) population. For this study, we included all children admitted to the neonatal ICU (NICU), pediatric ICU (PICU), or oncology (Onc) ward from March 2008 to March 2017 who underwent an ASP review. Unadjusted differences in LOS, mortality, readmissions, and HO-CDI were compared between cases of ASP agreement and disagreement. Generalized linear mixed models were used to control for potential confounders and account for patients with >1 ASP review. Results: ASP performed 11, 545 antimicrobial reviews (PICU 3, 628; NICU 2, 824; Onc 5, 093) on 7, 329 unique patients. ASP provided 2, 088 recommendations. Stop antibiotics was the most common recommendation ( N = 1, 045; 50%) followed by narrow antibiotics ( N = 474; 23%), and obtain an infectious disease consultation ( N = 334; 16%). Agreement with ASP by the prescribing clinician occurred in 70% of cases. Overall, 356 (5%) patients died, 87 (1%) had HO-CDI, and 2, 608 (36%) were readmitted. Agreeing with an ASP recommendation was not associated with increased odds of mortality or readmission. Agreement with an ASP recommendation was not associated with decreased odds of acquiring HO-CDI (adjusted OR 1.58, 95% CI: 0.35, 7.26). Among HR patients with a single ASP review, the median LOS was significantly shorter for clinicians who agreed with recommendations vs. disagreed (10.3 days vs. 12.5 days, respectively, P = 0.02). Conclusion: Agreement with an ASP recommendation was associated with a shorter LOS and no increase in readmissions or mortality. Further stewardship strategies are needed to optimize antimicrobial use in this HR pediatric population. Disclosures: All authors: No reported disclosures.